O espaço-tempo da espera nos contos de Mia Couto: uma perversa fábrica de ausências. - Marques., Moama Lorena de Lacerda (2013)
Our thesis has eight stories written by Mozambican Mia Couto in its corpus, which were selected from four different books: from Cronicando (1991), A velha e a aranha , from Estórias abensonhadas (1994), O perfume , from Na berma de nenhuma estrada e outros contos (2001), the homonymous narrative: Na berma de nenhuma estrada , and from O fio das missangas the other four short stories: A saia almarrotada , Inundação , A despedideira and O cesto . In all of them, we come across female protagonists who find themselves in situations of waiting, most of them related to a male character: son, husband, lover. The starting point for the proposition of the research was the finding that waiting is the generating and conducting theme of the narratives, real determiners for the constitution of its elements, particularly, in time and space. According to this observation, we have aimed to study the times and spaces of waits of the female characters. The basis theory which supports the analysis is the Bakhtinian chronotopes, which correlates time and space in an inseparable way, however, observing them also in relation to other elements of the narrative. Nonetheless, other theoretical and critical studies were also of great importance to the basement of our analyzes, among which, we highlight the main ones: the studies about the intimate space of the house made by Bachelard (2005), the discussions on the functions of space in literature by Osman Lins (1976), the research on the cyclic time in the works of Portuguese writers held by Isabel Allegro de Magalhães (1987), a few representative authors of Cultural Studies, such as by Stuart Hall (2011) and Homi Bhabha (2010), among others, including those who, in their writings, provide important contributions to the understanding not only the works by Mia Couto, but also of the Mozambican short stories in general, as the thesis developed by Maria Fernanda Afonso (2004). As for the results, we have found out that the chronotope of the short stories analyzed is an "intimate space in a cyclical time of waits." This intimate space will be represented mainly by the house, as well as by what we call border chronotopes, taking the road as an example, since even when the characters circulate outdoor spaces, yet they speak of an intimacy strongly related to theme of waiting.